Molecular epidemiology of hepatitis B and hepatitis D in Kelantan, Malaysia - Eneye, Bello Kizito (2025)
The global burden of hepatitis B virus (HBV) and hepatitis D virus (HDV) is still of epidemiological significance. The molecular epidemiology of HBV and HDV in Malaysia has yet to be well documented. This study aims to determine the molecular epidemiology of HBV and HDV among a chronic HBV cohort in Kelantan and the associated HBV drug mutation within Kelantan. Blood samples were collected from 226 chronic HBV patients in Kelantan and screened for HBV and HDV antiantibodies using an enzyme-linked immunosorbent assay (ELISA) technique. DNA/RNA was extracted from the samples, and the HDV RNA was converted to cDNA using a cDNA synthesis kit. The DNA/cDNA of the subjects were amplified using a nested PCR method. All amplicons were electrophoresed and sequenced. The sequences were typed using Phylogenetic tree and subtyping tools into their respective genotypes, subtypes, and serotypes accordingly. Three HBV genotypes (HBV genotypes B, C, and D) and two recombinant HBV genotypes (HBV genotype B/A and HBV genotype B/C) were discovered to be in circulation within Kelantan. HBV genotype B had the highest prevalence (93.0%), while HBV genotype D had the lowest prevalence (1.0%). HBV sub-genotype B3 (31.0%) had the highest occurrence in Kelantan. Evolutionary dynamics of HBV reveal different serotypes of HBV in circulation within the study population. Serotype adw (54.0%) was the predominant serotype in this study. Two HDV genotypes [HDV genotype I (40.0%) and HDV genotype II (60.0%)] were in circulation in Kelantan. The phylogenetic time tree revealed that HBV genotype B dates back approximately 400 years ago, while HBV genotypes C and D were relatively recent, 40 years and 11 years, respectively. HDV genotypes were in the genomic pool approximately 40 years ago. Kota Bharu, Tumpat, and Kuala Krai were the geographic risk regions for acquiring HBV and HDV genotypes. Age, Occupation, gender, marital status, and biochemical markers (Total and direct bilirubin, AST, and ALP) were discovered to be predisposing risk factors in acquiring HBV and HDV genotypes within Kelantan at P<0.05. There was evidence of drug-associated resistance among the naïve and treated patients included in this study. Lamivudine drug resistance was the highest (26.6%), while tenofovir resistance was the lowest (9.04%). The prevalence of HBV genotypes and evolutionary diversity in Kelantan is of epidemiological significance, and genomic surveillance and monitoring should be implemented. The presence of HDV in Kelantan stresses the need for routine HDV surveillance and monitoring in Kelantan and Malaysia.